Effect of Trichoderma viride pre‐inoculation in pine species with different levels of susceptibility to Fusarium circinatum: physiological and hormonal responses. (3rd September 2019) - Amaral, J.; Pinto, G.; Flores‐Pacheco, J. A.; Díez‐Casero, J. J.; Cerqueira, A.; Monteiro, P.; Gómez‐Cadenas, A.; Alves, A.; Martín‐García, J.
Abstract : Pine pitch canker (PPC), caused by Fusarium circinatum, affects Pinus species worldwide. Although no effective solutions have yet been found to control it, there is a growing interest in using biological control agents (BCA) such as Trichoderma to avoid the application of chemical‐based products. Using species with an increasing level of susceptibility to PPC ( Pinus pinea, Pinus pinaster and Pinus radiata ), this study aimed to evaluate the effect of Trichoderma viride pre‐inoculation on disease development, assessing several physiological and hormonal parameters. A 2‐week period elapsed between T. viride and F. circinatum inoculation. Sampling for each species was performed independently when at least 50% of the plants of one of the inoculated groups developed disease symptoms. Fusarium circinatum infection reduced water status and photosynthesis, but increased proline, abscisic acid and jasmonic acid concentrations in plants of P. radiata and P. pinaster with symptoms; while in P. pinea water relations were maintained and anthocyanin accumulation occurred in the presence of F. circinatum . In P. radiata, T. viride pre‐inoculation accelerated disease progression, with some PPC‐induced responses augmented (decreased water potential and photosynthesis; increased substomatal CO2 concentration) and novel changes not found in seedlings inoculated exclusively with F. circinatum (increased electrolyte leakage and salicylic acid; decreased relative water content). This suggests that T. viride may be initially recognized as an invading organism, subverting the plant defence mechanisms for successful root colonization. If seedlings are not allowed to recover from this state, pathogen infection may thus be facilitated, highlighting the importance of application timing in BCA strategies.